2017
DOI: 10.5603/njo.2017.0010
|View full text |Cite
|
Sign up to set email alerts
|

Proton radiotherapy should be further developed in Poland

Abstract: Proton radiation therapy needs to be further developed in Poland by virtue of both epidemiological considerations and because this type of radiation exhibits very advantageous biological and physical properties. The underlying benefit of such therapy is to make lower integral radiation dose delivered to structures beyond a given target area, including critical organs, resulting in reduced toxicities for patients. Of somewhat less import is the improvement in dose distributions for target areas (vs photons), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…However, not all institutions were found to be properly equipped. A 2015 study reported that only 28% of hospitals and 2% of specialist ambulatory providers participating were able to provide laboratory tests, CT and MRI scans, and endoscopy examinations; fewer than half of the audited providers could undertake the intraoperative pathology necessary to assess the margins of some tumor excisions [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all institutions were found to be properly equipped. A 2015 study reported that only 28% of hospitals and 2% of specialist ambulatory providers participating were able to provide laboratory tests, CT and MRI scans, and endoscopy examinations; fewer than half of the audited providers could undertake the intraoperative pathology necessary to assess the margins of some tumor excisions [24].…”
Section: Resultsmentioning
confidence: 99%
“…The national screening programs for breast, cervical, and colorectal cancers, were introduced as part of the National Program for Cancer Disease Control in 2006 and extended through 2015 and was later renewed for 2016-24 [31]. However, a pilot from 2018 reported 16% for breast, 20% for cervical, and 40% for colorectal cancer screening [24]. While the oldest old fall outside the boundaries of breast cancer screening, diagnostic testing of breast cancer should not be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high costs many studies show that PBT is cost effective in terms of treatment complications and indirect costs. [2] Currently, PBT is used in a very small number of cancers. Most countries use PBT in the pediatric population, where the incidence of radiation-related complications is relatively higher due to the longer life expectancy and the higher sensitivity of healthy tissues to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…According to forecasts, by 2025 an increase in the incidence of cancer in Poland is expected from 310,000 up to 350,000. [2] e aim of the study was to evaluate a budget impact of PBT from the public payer perspective in Poland. [5] METHODS e budget impact analysis (BIA) concerns the nancial consequences of extending the use of PBT from the perspective of the Polish public payer (National Health Fund, NHF) in 9 oncological indications in pediatric population (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that by the end of 2025 the number of new cases in Poland will increase to 350,000 annually. [6]…”
Section: Introductionmentioning
confidence: 99%